ADAlılar | Issue 4 | January 2022 ﻿ - Javadov, Samir; Zeynalov, Rifah; Aliyeva, Aylin; Huseynova, Gunel; Ismayilova, Nurel (ADA University, 2022)
I remember the time when I was fifteen, glossy magazines were a rarity. Some people brought them from abroad, some bought on a black market. I was always impressed by bright and high-quality pictures that showed beautiful and happy faces (mostly foreigners), expensive cars, or scarce goods which you could hardly have seen in your life. Publishing by school students their own a magazine was something out of fantasy. We could only dream of it. The best thing that we could have done was to create was a wall newspaper. We simply took a piece of Whatman paper, and one of us who had a better handwriting, wrote on it. We also added some drawings, made by colored pencils. Time has passed, and everything has changed now. Publishing a school magazine is no longer a dream. ADA school students have been publishing their own magazine, ADAlilar, since 2019, right after the school was founded. And here we are with our fourth edition! With new, dedicated, inquiring, and creative team, interesting stories, poems, wonderful interviews, photographs, and many other things ADAlilar wanted to share with you. I would like to express my gratitude to heads of divisions of the editorial board and their teams, to everyone who contributed to this issue of ADAlilar School Magazine. I am also grateful to ADA School’s English instructor Ms. Regsana Kerimova for her help with editing and proofreading. I have to thank tens of students for their support. Samir Javadov Editor-in-Chief ADAlilar School Magazine
Keywords: ADA School -- Magazine